Pemberdayaan UMKM melalui Diversifikasi Olahan Pangan Lokal Berbasis Ubi Kayu dan Jagung di Nagari Sarilamak Kecamatan Harau - Annisa Ulhusna; Rivo Yulse Viza; Mimi Harni; Rilma Novita; Yenni M (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2026)
Community service activities play an important role in improving community capacity through the application of technology. This activity aimed to enhance the knowledge and skills of members of UMKM Bundo Kanduang in Jorong Purwajaya, Nagari Sarilamak, Kecamatan Harau, Kabupaten Lima Puluh Kota in processing local food commodities, namely cassava and corn, to become more valued products. The methods used in this program included socialization, counseling, and hands-on training. The training materials covered the processing of corn sticks, cassava-based nugget-like products, mocaf flour, and corn donuts. This activity involved 18 participants and was conducted in several stages. The results showed an improvement in participants’ understanding of local food diversification as well as their technical skills in food processing. Participants were able to produce products with good characteristics, which indicates that they can produce them correctly. This activity also encouraged the use of local resources and opened opportunities for food-based businesses. Therefore, the application of simple food processing technology can be an effective strategy to increase the economic value of local commodities and support community empowerment.